Intermittent low-intensity and moderate-intensity exercise effects on cognition in community-dwelling older adults: a pilot study exploring biological mechanisms - Gujral, Swathi; Cameron, Judy L.; Conaty, Kayla; Ziady, Sumer; Sahu, Amrita; Jakicic, John M.; Rogers, Renee J.; Rosano, Caterina; Vallejo, Abbe N.; Erickson, Kirk I.; Ibrahim, Tamer S.; Aizenstein, Howards; et al. (Frontiers in Aging Neuroscience, 2024)
Background/Objective: To examine the cognitive benefits of 6 months of prescribed intermittent exercise (10minute bouts totaling 150 weekly minutes) in community-dwelling older adults, comparing effects of lowintensity movement (LIM) and moderate-intensity aerobic exercise (aerobic exercise; AE) training; and exploring biological mechanisms of exercise-related cognitive improvement. Method: Twenty-five adults (> 60 years old) participated in a 6-month controlled trial and were randomized into LIM or AE intermittent training. Cognition was assessed using a neuropsychological test battery including the Repeatable Battery for the Assessment of Cognitive Status (RBANS), California Verbal Learning Test, 2 nd Edition (CVLT-II), and Delis-Kaplan Executive Function System (D-KEFS). Neuroimaging measures were collected using a 7T human MRI scanner. Serologic neurotrophic and inflammatory factors were analyzed using Luminex multiplex assays (brain derived neurotrophic factor (BDNF); vascular endothelial growth factor (VEGF)); interleukin-6 (IL-6), C-reactive protein (CRP), plasminogen activator inhibitor (PAI-1). Results: LIM and AE intermittent training had dissociable effects on cognition, with LIM resulting in improved learning and memory and AE resulting in improved executive functioning. Intervention groups differed on change in cognitive performance on CVLT-II learning and D-KEFS trail making test. Increase in right dorsolateral prefrontal cortex (DLPFC) surface area was linked to executive improvement (i.e., phonemic fluency) regardless of intervention group. A decline in circulating PAI-1 was linked to learning and memory improvement in response to LIM over 6 months. Conclusions: Moderate-intensity AE and LIM intermittent training likely have distinct cognitive benefits, though low-intensity activity is often included as a control group in exercise trials in aging.